2000
DOI: 10.2337/diabetes.49.11.1783
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of MAPK cascades by insulin and osmotic shock: lack of an involvement of p38 mitogen-activated protein kinase in glucose transport in 3T3-L1 adipocytes.

Abstract: Osmotic shock and insulin stimulate GLUT4 translocation and glucose transport via mechanisms that are for the most part distinct yet convergent. In this article, we investigated the effect of osmotic shock and insulin on the activation of the mitogen-activated protein kinase (MAPK) cascades in differentiated 3T3-L1 adipocytes. The MAPKs are activated by phosphorylation on conserved tyrosine and threonine residues. Both sorbitol and insulin strongly stimulated extracellular regulated kinase (ERK) 1 and 2 phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 62 publications
(57 reference statements)
7
52
1
Order By: Relevance
“…Both of JNK and p38 inhibitors (SP600125 and SB203580) could attenuate MBS-induced apoptosis. The JNK and p38 inhibitors (SP600125 and SB203580) specifically inhibit JNK and p38 catalytic activity respectively by binding to the ATPbinding pocket preventing the activation of downstream factors, but p38 inhibitor SB203580 does not result in the decreased phosphorylation levels of p38 (Kayali et al, 2000;Bennett et al, 2001). Here, we also found that SP600125 (a specific inhibitor of JNK) inhibited JNK activation, but SB203580 (a specific inhibitor of p38) had no effect on p38 activation.…”
Section: Discussionsupporting
confidence: 63%
“…Both of JNK and p38 inhibitors (SP600125 and SB203580) could attenuate MBS-induced apoptosis. The JNK and p38 inhibitors (SP600125 and SB203580) specifically inhibit JNK and p38 catalytic activity respectively by binding to the ATPbinding pocket preventing the activation of downstream factors, but p38 inhibitor SB203580 does not result in the decreased phosphorylation levels of p38 (Kayali et al, 2000;Bennett et al, 2001). Here, we also found that SP600125 (a specific inhibitor of JNK) inhibited JNK activation, but SB203580 (a specific inhibitor of p38) had no effect on p38 activation.…”
Section: Discussionsupporting
confidence: 63%
“…This occurred concomitant with an increase in phosphorylation of the ERK-dependent phosphorylation site S380 of RSK as well as an increase in ERK phosphorylation. Although ERK has previously been shown to be phosphorylated in response to osmotic shock in some cells [42], p90RSK is normally not thought to participate in this response [43]. This may therefore represent a cell type specific response to ES cells and it will be interesting to determine the significance of this.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway is activated by many stimulatory agents and phosphorylates downstream signaling molecules (16). Insulin also activates MAPK (24,32,49), and MAPK activation leads to Hsp27 phosphorylation (1,25,35,39,63). Thus, in the present study, we used phosphospecific antibodies to detect phosphorylated isoforms of Hsp27.…”
Section: Discussionmentioning
confidence: 99%
“…Once insulin activates the insulin receptor, the PI3K/Akt and MAPK pathways are activated (55). Recent evidence indicates that insulin activates ERK1/2 and p38 MAPK (3,25,35,41). p38 MAPK, in turn, activates MAPKAPK-2 that directly regulates the phosphorylation of Hsp27 (1,39,69).…”
Section: Discussionmentioning
confidence: 99%